Clara Barton papers - Barton, Clara, 1821-1912.
Correspondence, diaries and journals, reports, addresses, legal and financial papers, organizational records, lectures, writings, scrapbooks, biographical material, printed matter, memorabilia, and other papers relating to Barton's work to provide relief services during the Civil War and the Franco-Prussian War, the work of the American National Red Cross which she founded, and the National First Aid Association of America.
Subjects include the Office of Correspondence of Friends of the Missing Men of the U.S. Army, speaking tour of Barton and former Andersonville prisoner Dorence Atwater concerning the identification of graves at Andersonville Prison, Barton's civilian relief effort in cooperation with the International Committee of the Red Cross during the Franco-Prussian War, the passage of the Geneva Convention, the International Red Cross Committee, the founding and administration of the American National Red Cross, the protection of Red Cross insignia, Red Cross Park, the congressional investigation into Barton's stewardship, the Red Cross's response to appeals for aid from victims of natural disasters and war, stateside camp service during the Spanish-American War, Harriette L. Reed's role in the National First Aid Association of America, progressive movements, women's rights, woman suffrage, temperance, and other reform issues.
Correspondents include Barton's family members, local chapters of the American Red Cross, Alvey A. Adee, Susan B. Anthony, P. Louis Appia, Dorence Atwater, Harriet N. Austin, E. Florence Barker, Stephen E. Barton, William Eleazar Barton, Henry W. Bellows, Mabel T. Boardman, Samuel W. Briggs, Lucy Hall Brown, Lucien Burleigh, Mary Weeks Burnett, Benjamin F. Butler, Henry Dunant, Edmund Dwight, Frances Dana Gage, Joseph Gardner, Minna Kupfer Golay, Lucy M. Graves, Leonora B. Halsted, John Hitz, Mary Seymour Howell, Julian B. Hubbell, International Committee of the Red Cross, Samuel M. Jarvis, George Kennan, Mrs. John A. Logan, Luise, Grand Duchess of Baden, Antoinette Margot, William McKinley, Gustave Moynier, Ellen Spencer Mussey, Richard Olney, Walter P. Phillips, George H. Pullman, Joseph Sheldon, Adolphus S. Solomons, F.R. Southmayd, Sara J. Spencer, Edwin McMasters Stanton, Elvira Stone, Harriet Taylor Upton, Bernard B. Vassall, Charlotte Fowler Wells, Mary Isabelle (Kensel) Wells, Roscoe Green Wells, Frances Elizabeth Willard, Mary Bannister Willard, and Henry Wilson.
Available through the Library of Congress Web site.
Microfilm edition of a portion of these papers available
Microfilm edition produced from originals in Manuscript Division.
Library of Congress Geography and Map Division.
Library of Congress Prints and Photographs Division.
Philanthropist, nurse, educator, and lecturer. Founded American Red Cross in 1881 and National First Aid Association of America in 1905.
Keywords: Adee, Alvey A. -- 1842-1924 -- Correspondence; Anthony, Susan B. -- 1820-1906 -- Correspondence; Appia, P. L. -- 1818-1898 -- Correspondence; Atwater, Dorence, -- 1845-1910 -- Correspondence; Austin, Harriet N. -- Correspondence; Barker, E. Florence -- Correspondence; Barton, Stephen E. -- 1848- -- Correspondence; Barton, William Eleazar, -- 1861-1930 -- Correspondence; Bellows, Henry W. -- 1814-1882 -- Correspondence; Boardman, Mabel Thorp, -- 1860-1946 -- Correspondence; Briggs, Samuel W. -- Correspondence; Brown, Lucy Hall, -- -1907 -- Correspondence; Burleigh, Lucien, -- 1817-1884 -- Correspondence; Burnett, Mary Weeks -- Correspondence; Butler, Benjamin F. -- 1818-1893 -- Correspondence; Dunant, Henry, -- 1828-1910 -- Correspondence; Dwight, Edmund, -- 1824- -- Correspondence; Gage, Frances Dana, -- 1808-1884 -- Correspondence; Gardner, Joseph, -- 1833-1919 -- Correspondence; Golay, Minna Kupfer -- Correspondence; Graves, Lucy M. -- Correspondence; Halsted, Leonora B. -- Correspondence; Hitz, John, -- 1828-1908 -- Correspondence; Howell, Mary Seymour, -- 1844-1913 -- Correspondence; Hubbell, Julian B. -- 1847-1929 -- Correspondence; Jarvis, Samuel M. -- 1853-1913 -- Correspondence; Kennan, George, -- 1845-1924 -- Correspondence; Logan, John A., -- Mrs., -- 1838-1923 -- Correspondence; Luise, -- Grand Duchess, consort of Frederick I, Grand Duke of Baden, -- 1838-1923 -- Correspondence; Margot, Antoinette, -- 1843-1925 -- Correspondence; McKinley, William, -- 1843-1901 -- Correspondence; Moynier, Gustave, -- 1826-1910 -- Correspondence; Mussey, Ellen Spencer, -- 1850-1936 -- Correspondence; Olney, Richard, -- 1835-1917 -- Correspondence; Phillips, Walter P. -- 1846-1920 -- Correspondence; Pullman, George H. -- Correspondence; Reed, Harriette L., -- -1920 -- Correspondence; Sheldon, Joseph, -- 1828-1911 -- Correspondence; Solomons, Adolphus S. -- 1826-1910 -- Correspondence; Southmayd, F. R. -- Correspondence; Spencer, Sara J. -- 1837-1909 -- Correspondence; Stanton, Edwin McMasters, -- 1814-1869 -- Correspondence; Stone, Elvira -- Correspondence; Upton, Harriet Taylor -- Correspondence; Vassall, Bernard B. -- 1835-1894 -- Correspondence; Wells, Charlotte Fowler, -- 1814-1901 -- Correspondence; Wells, Mary Kensel -- Correspondence; Wells, Roscoe Green, -- 1878- -- Correspondence; Willard, Frances E. -- 1839-1898 -- Correspondence; Willard, Mary Bannister, -- 1841- -- Correspondence; Wilson, Henry, -- 1812-1875 -- Correspondence; Barton family -- Correspondence; American National Red Cross; Andersonville Prison; Friends of the Missing Men of the United States Army. -- Office of Correspondence; International Committee of the Red Cross; National First Aid Association of America; Geneva Convention -- (1864); Ambulance service; Disaster relief